IMPATT integrated active microstrip antenna - Nayak A.; Vishvakarma B.R. (My University, 2025)
An IMPATT diode integrated rectangular patch is theoretically investigated based on the circuit concept in the millimetre range. The various parameters of the antenna are found to depend on the bias voltage and there is marked improvement in the tuning range, radiated power and bandwidth. The antenna exhibits bandwidths of 20% for 1.5:1 VSWR and 35% for 2:1 VSWR. The antenna shows frequency agility for a band of 614 MHz, i.e. 1.7837 % band.